ÇALIŞANLARIN YÖNETİCİLERİNE İLİŞKİN ALGILADIKLARI PSİKOPATİ ÖZELLİKLERİNİN SERGİLEDİKLERİ SİNİK DAVRANIŞLAR ÜZERİNDEKİ ETKİSİ - (:unkn) unknown (My University, 2019)
Örgütlerde yöneticilerin sergiledikleri çeşitli davranışların çalışanlar üzerine olumlu ya da olumsuz yönde etkilerinin olduğu bilinmektedir. Bu araştırma, çalışanların yöneticilerine yönelik algıladıkları psikopati davranışlarının, gösterdikleri sinik davranışlar (örgütsel sinizm) üzerindeki etkisini incelemek amacıyla gerçekleştirilmiştir. Yapılan araştırma için 4 farklı ilde toplam 242 katılımcıya gönüllü katılım esasına dayanan anket çalışması uygulanmıştır. Katılımcılar sektör farkı gözetilmeksizin (kamu veya özel) rassal olarak belirlenmiştir. Elde edilen veriler SPSS paket programı ile analiz edilmiştir. Normal dağılıma uygun olduğu tespit edilen verilere; geçerlilik analizi, güvenilirlik analizi ve regresyon analizleri uygulanmıştır. Analizlerden elde edilen bulgulara göre, çalışanların yöneticilerine ilişkin algıladıkları psikopati özelliklerinin, sergiledikleri örgütsel sinizm davranışının 3 faktörü üzerinde de (bilişsel sinizm, duyuşsal sinizm, davranışsal sinizm) etkisi olduğu ancak en yüksek etkinin duyuşsal sinizm boyutu üzerine olduğu saptanmıştır.

In recent years, especially in organizational behavior literature, studies are carried out in areas such as personality, bright and dark sides of personality, organizational cynicism. It is known that various behaviors displayed by the managers in the organizations have positive or negative effects on the employees. This study was carried out to examine the effect of psychopathic behaviors of managers perceived by employees on the organizational cynicism behavior (cognitive cynicism, affective cynicism, behavioral cynicism) of employees. While there are many studies related to the dark side of personality in international literature, there is a limited number of studies specific to the Turkish case, but there is no study that is directly related to psychopathy. However, in the literature there are some work that underline the effects of psychopathic behavior, such as lack of moral values, lack of remorse and uncontrolled behavior, on organizational life (Arrigo & Shipley, 2001). Some Turkish-specific studies like Özsoy et al. (2017) and Özsoy and Ardıç (2017) find that psychopathy negatively affects the trust in managers and reduces job satisfaction, respectively. Besides, Çalışkan et al. (2015) find a statistically significant and negative relationship between the perceived cultural intelligence of the leaders and the behavior of organizational cynicism. Another study conducted by Erkutlu and Chafra (2017) shows that narcissistic characteristics of the leaders have a statistically significant and positive effect on organizational cynicism. As a result of the detailed examinatio carried out in national and international literature, there is no study examining the effect of managers psychopathic features on the employees organizational cynicism behaviors. In this context, this issue is considered as the subject of study with the idea that managers with psychopathy characteristics will be effective on organizational cynicism. In this respect, the hypotheses of the research was determined as follows: H1: The perceived psychopathy characteristics of managers by employees have an effect on organizational cynicism behaviors. H2: The perceived psychopathy characteristics of managers by employees have an effect on the cognitive dimension of organizational cynicism. H3: The perceived psychopathy characteristics of managers by employees have an effect on the affective dimension of organizational cynicism. H4: The perceived psychopathy characteristics of managers by employees have an effect on the behavioral dimension of organizational cynicism. The sample of the study consists of people working in the public or private sectors in four different provinces in Turkey (İstanbul, Bursa, Samsun and İzmir). Data were collected between 2016-2017. The survey was used as data collection tool and 242 valid surveys from 300 surveys were included in the study. The analysis is conducted via SPSS program. As a result of the regression analysis, all of the hypotheses are accepted. In this respect, it was determined that the perceived psychopathy characteristics of the managers had a statistically significant and positive effect on all three dimensions of organizational cynicism. However, the highest effect was found to be on behavioral cynicism. The findings of the study are consistent with the results of the study conducted by Erkut and Chafra (2017) who examined the effect of the narcissistic characteristics of the leaders on organizational cynicism. Although there is no study between organizational cynicism and the leaders who have machiavellianism, which is another sub-dimension of dark personality traits, if the findings of Erkut and Chafra’s study and the results of the research we conducted are considered together; a more general conclusion can be made that managers with dark personality traits will increase organizational cynicism. Other researchers who want to do research on this subject can examine the relationship between managers’ machiavellianism behaviours and organizational cynicism. Thus, research findings on this subject will help to generalize the results.
THE EFFECT OF PSYCHOPATHIC BEHAVIORS OF MANAGERS PERCEIVED BY EMPLOYEES ON ORGANIZATIONAL CYNICISM